2021
DOI: 10.1097/md.0000000000024862
|View full text |Cite
|
Sign up to set email alerts
|

Smell disorders in COVID-19 patients: role of olfactory training

Abstract: Background: As the coronavirus disease 2019 (COVID-19) spread around the world, a surge of evidence suggests that smell disorders are common symptoms in COVID-19 infection. This dysfunction may cause loss of appetite, malnutrition, poisoning, and depression. Obviously, the impairment has a strong impact on the quality of life. Therefore, there is an urgent need to identify effective treatments. Various therapies have been studied to treat smell disorders after infection, and olfactory training (OT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…In this study, we observed that the adherence to an olfactory training protocol was significantly associated with higher values of Sniffin’ Sticks test scores at 18 months post infection. The efficacy of olfactory training in COVID‐19 patients was supported by a recent meta‐analysis, but this paper only included studies investigating short‐term recovery (<1 year) [ 32 ]. The present paper may suggest a positive impact of olfactory training over the mid‐to‐long term, but future controlled studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed that the adherence to an olfactory training protocol was significantly associated with higher values of Sniffin’ Sticks test scores at 18 months post infection. The efficacy of olfactory training in COVID‐19 patients was supported by a recent meta‐analysis, but this paper only included studies investigating short‐term recovery (<1 year) [ 32 ]. The present paper may suggest a positive impact of olfactory training over the mid‐to‐long term, but future controlled studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study highlighted the high incidence of olfactory impairment in children with congenital sCMV infection. As olfactory loss can impact nutrition, social interaction, safety and quality of life, early detection of olfactory disorders may lead to olfactory rehabilitation programs in order to limit neurodevelopmental consequences: recent studies have demonstrated the importance of olfactory training to improve the olfactory function in adults [27,28] and children [29].…”
Section: Discussionmentioning
confidence: 99%
“…Visual-olfactory training improved the levels of olfactory threshold, discrimination, and identification in another study [ 44 ]. Considering the relatively successful impact of the training, a systematic review is currently in progress focusing on COVID-19 induced chemosensory dysfunction [ 45 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%